2020
DOI: 10.1007/s40801-020-00194-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Oritavancin for the Treatment of Osteomyelitis

Abstract: Osteomyelitis is a difficult-to-treat disease that can require both surgical debridement and a prolonged course of antimicrobial therapy. Current standard of care for the antimicrobial treatment of osteomyelitis is fraught with multiple challenges and limitations. Patients typically require the insertion of an indwelling catheter for single or multiple daily intravenous antibiotic infusions for up to 6 weeks. Currently, there are treatment guidelines for only vertebral osteomyelitis, indicating the complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
(60 reference statements)
0
14
0
2
Order By: Relevance
“…Its high protein-binding (85-905) and the prolonged terminal half-life (200-300 h) permits the administration of a single dose of 1,200 mg with good therapeutical levels beyond two weeks 155 and a good activity in biofilms 156 . After the initial dose of 1,200 mg, sequentially doses of 800 mg can be administered weekly for infections that will require a more prolonged treatment such as osteomyelitis 157 Elimination of oritavancin mainly occurs through the reticuloendothelial system, thus no adjustments of dosage are needed in the cases of renal or hepatic failure. Notably, oritavancin is a weak inhibitor of CYP2C9 and CYP2C19, and an inducer of CYP3A4 and CYP2D6, thus drug-drug interactions (e,g,, patients treated with warfarin) should always considered.…”
Section: Dalbavancin and Oritavancinmentioning
confidence: 99%
“…Its high protein-binding (85-905) and the prolonged terminal half-life (200-300 h) permits the administration of a single dose of 1,200 mg with good therapeutical levels beyond two weeks 155 and a good activity in biofilms 156 . After the initial dose of 1,200 mg, sequentially doses of 800 mg can be administered weekly for infections that will require a more prolonged treatment such as osteomyelitis 157 Elimination of oritavancin mainly occurs through the reticuloendothelial system, thus no adjustments of dosage are needed in the cases of renal or hepatic failure. Notably, oritavancin is a weak inhibitor of CYP2C9 and CYP2C19, and an inducer of CYP3A4 and CYP2D6, thus drug-drug interactions (e,g,, patients treated with warfarin) should always considered.…”
Section: Dalbavancin and Oritavancinmentioning
confidence: 99%
“…Of note, in the SOLO-2 study, five cases of osteomyelitis were reported as adverse events in the oritavancin group; therefore, osteomyelitis is listed as a warning for oritavancin, even though these events occurred within the first 9 days after drug initiation, suggesting that it may have been already present [ 69 , 72 ]. However, retrospective data, case series and real-world data suggested that oritabancin is both safe and effective in the management of osteomyelitis [ 73 77 ]. Therefore, the role of this agent in the management of diabetic foot infection is currently unclear.…”
Section: Lipoglycopeptidesmentioning
confidence: 99%
“…Оритаванцин проявлял выраженную активность с диапазоном МПК от 0,03 мкг/мл до 0,5 мкг/мл при МПК₉₀ 0,25 мкг/мл, что подчёркивает потенциальную возможность его использования для лечения инфекций, вызываемых ванкомицин-и даптомициноустойчивыми энтерококками. На сегодняшний день оритаванцин официально не разрешён для применения в медицинской практике для лечения инфекций, вызванных ванкомицинрезистентными энтерококками, хотя клинические наблюдения использования off-label в клинической практике этого антибиотика демонстрируют его эффективность [6,24]. Опыты по моделированию фармакодинамики и эксперименты на инфекционных моделях cо штаммами VRE также свидетельствуют об эффективности данного антибиотика [25,26].…”
Section: результаты и обсуждениеunclassified
“…На сегодняшний день новые липогликопептиды являются альтернативой для лечения осложнённых форм стафилококковых инфекций, однако пока рекомендованы для лечения инфекций кожи и мягких тканей. Тем не менее, в ряде работ было показано, что липогликопептиды эффективны для терапии остеомиелитов [6], бактериемий и эндокардитов [7,8]. Целью исследования стала сравнительная оценка чувствительности коллекции клинических грамположительных изолятов, циркулирующих в России, к липогликопептидным антибиотикам.…”
Section: Introductionunclassified